2023
DOI: 10.3390/ijms24065816
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Epidermal Growth Factor Receptor Overexpression as a Survival Predictor in Oral Squamous Cell Carcinoma

Abstract: The aim of this study was to determine, by immunohistochemical methods, the expression of nEGFR and markers of cell proliferation (Ki-67), cell cycle (mEGFR, p53, cyclin D1), and tumor stem cells (ABCG2) in 59 pathohistological samples of healthy oral mucosa, 50 oral premalignant changes (leukoplakia and erythroplakia), and 52 oral squamous cell carcinomas (OSCC). An increase in the expression of mEGFR and nEGFR was found with the development of the disease (p < 0.0001). In the group of patients with leukop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…The stained sections were then observed under high magnification (40x), with computer assisted image analyzer (LAS Version-4.1) for cytoplasmic staining and Allred (Quick) scoring system was used to analyze immunohistochemical expression. 17 , 18 , 19 In the Allred scoring system score A depicts the proportion of positively stained cells out of hundred it ranges from 0 to 5 (0 = 0%, 1 = 1 %, 2 = 2–10%, 3 = 11–33%, 4 = 34–66%, 5 = 67–100%) and score B depicts the intensity of the stain which ranges from 0 to 3 (0 = Negative, 1 = Weak, 2 = Intermediate and 3 = Strong). The combination of the percentage of positively stained cells and the staining intensity (A + B) ranges from 0 to 8, wherein 0-1 score is considered to be negative, 2–3 is weak, 4–6 is intermediate and 7–8 is considered to be strong positivity and as such a particular score can be assigned to the slide.…”
Section: Methodsmentioning
confidence: 99%
“…The stained sections were then observed under high magnification (40x), with computer assisted image analyzer (LAS Version-4.1) for cytoplasmic staining and Allred (Quick) scoring system was used to analyze immunohistochemical expression. 17 , 18 , 19 In the Allred scoring system score A depicts the proportion of positively stained cells out of hundred it ranges from 0 to 5 (0 = 0%, 1 = 1 %, 2 = 2–10%, 3 = 11–33%, 4 = 34–66%, 5 = 67–100%) and score B depicts the intensity of the stain which ranges from 0 to 3 (0 = Negative, 1 = Weak, 2 = Intermediate and 3 = Strong). The combination of the percentage of positively stained cells and the staining intensity (A + B) ranges from 0 to 8, wherein 0-1 score is considered to be negative, 2–3 is weak, 4–6 is intermediate and 7–8 is considered to be strong positivity and as such a particular score can be assigned to the slide.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that p53 is significantly more expressed in patients with premalignant changes and OSCC compared to healthy oral mucosa and that its expression is associated with perineural invasion (PNI). Cyclin D1 expression was significantly higher in patients with premalignant changes and OSCC compared to healthy oral mucosa, suggesting its role in disease progression [ 27 ].…”
mentioning
confidence: 99%